ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI DESA MINTI MAKMUR KECAMATAN RIOPAKAVA KABUPATEN DONGGALA - Januar, Moh; Alam, Max Nur; Effendy, Effendy (AGROTEKBIS, 2017)
This research aimed to identify the factors that affect the production and the amount of income on wetlandrice farmin Minti Makmur Village Riopakava Subdistrict Donggala Regency. The determination of respondents was carried out through Simple Random Sampling Method. The number of samples was 31 people taken from a population of 102. The analytical tool used was the functional production analysis of Cobb-Douglass and income analysis. The results of the researchshowed that the area of land, seed,urea fertilizer, ponska fertilizer, while sp36 fertilizer and meanwhile significantly effected on the production of wetland rice farmat 95%. The results of the analysis indicated that the average income was in the amount of IDR.22,096,451.61/1.31ha/planting season orIDR. 16,867,538.77/ha/planting season. Key Words : Farming, income,production, wetland rice.